(3GdLQGFe GdeYdheGJjI YGHQI GdMOhO (B: s (3OQGSI ebGQfI (B/ s - (3eMeO MeO YeQ GdZjGKjfs; (3YeQ eMeO SGde s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2013)
(3GSJgOa gPG GdHMK OQGSI GdLQGFe GdeYdheGJjI YGHQI GdMOhO HOhdI bWQ h LeghQjI eUQ GdYQHjI OQGSI ebGQfI (B: (3Je ajg JbSje GdHMK Edi aUd JegjOj h KdGKI CHhGH h NGJeI TedJ GdfJGFL h GdJhUjGJ (B. (3aj GdaUd GdJegjOj YfjJ GdOQGSI Heaghe GdLQGFe GdeYdheGJjI h WHjYJgG h NUGFUgG (B. (3h aj GdHGH GdChd YQVJ GdOQGSI GdCMcGe GdYGeI dehGLgI GdLQGFe GdeYdheGJjI (B. (3h aj GdHGH GdKGfj GdPj NUU dOQGSI ELQGAGJ HMK h JMbjb GdLQGFe GdeYdheGJjI (B. (3h aj GdHGH GdKGdK JfGhd GdHMK eOi GSJLGHI GdJTQjYGJ GdhVYjI dEKHGJ GdLQGFe GdeYdheGJjI YGHQI GdMOhO HGdhSGFd GdMOjKIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2013s
(3HHdjhLQGajG(B: (3UaMGJ (B340-357s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdLQGFe GdeYdheGJjIs; (3GdeLQe GdeYdheGJjs; (3YGHQI GdMOhOs; (3LQjeI GdbPa HWQjb GdEfJQfJ s; (3LQjeI GdEQgGH GdEdcJQhfj s; (3CSGdjH hhSGFd ehGLgI GdLQGFe GdeYdheGJjI s; (3GdJYGhf GdOhdj s; (3ecGaMI GdLQGFe GdeYdheGJjI s; (3JSdje GdeLQejf s; (3GdOdjd GdEdcJQhfj s; (3GdOdjd GdLfGFj GdJbdjOj s; (3eSQM GdLQGFe GdeYdheGJjI ddJdHS s; (3JSdje GdeLQejf s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs